Constitutional Issues and Challenges of Local Government Administration in Nigeria: A Theoretical Discuss (Journal of Governance and Development (JGD), 2017)
The controversies over the operations of local government system of administration in Nigeria has become a major discuss recently. As a third tier of government, local government was introduced as a means of bringing governance closer to the people toward meeting the needs and aspirations of the people at grassroots level. However, since the entrenchment of this system of administration in the constitution, there have been series of controversies over the real position of local government under the authorities of statesand the government at the centre over the establishments, control and supervisions of its activities as enshrined in the sections 7 (1) and 8 (6) of the 1999 constitution. However, this article regrets to note that the gains made in local governments’ administration across Nigeria after series of reforms before the emergence of 1999 constitution have been depreciating especially with the controversial sections in the constitution. The paper delved critically into the factors that account for this oft-touted performances and discoveredthat contradictions in some sections of the constitutions accounted for the logjam. With theoretical approach in its analysis, the paper concluded that there is need to address the perceived contradictions in sections 7 (1) and 8 (6) of the 1999 constitution in order to reposition local government system in Nigeria towards enhancing its service delivery to the grassroots populace.